Методичні підходи до виділення ринкових ніш - Арестенко, Тетяна Вікторівна; Арестенко, Татьяна Викторовна; Arestenko, Tetiana; Арестенко, В. В. (My University, 2017)
UK: У статті досліджено основні передумови та критерії виділення ринкових ніш у сучасних умовах ведення вітчизняного бізнесу. Встановлено, що фактор перенасичення ринку одноманітними товарними пропозиціями та переорієнтація конкурентної боротьби з якісного кола до цінового унеможливлює розвиток середнього та малого бізнесу. Це доводить актуальність виявлення або створення нішових ринків як неохоплених великими підприємствами сегментів споживачів. Запропонована методика виділення ринкової ніші. EN: Purpose. To investigate and to formulate the methodical system to defining niche market. Results of research. This article introduces a methodical simulation framework for investigating the niche markets for innovative and modernized products. It clarifies how consumer preferences, business strategy, and level of competition on market interact during market development. The framework allows investigation of the effects of uncertainty and competitors behavior corresponding niche market strategies. The importance of competition promoting the progress along with being the real threat to the enterprise has been determined. The influence of different kinds of strategic marketing on the formation, storage and choosing market segment for enterprises activity has been investigated. Innovative firms can create products in response to or in anticipation of competitor’s product development policy, but true niche markets do not emerge unless there are also specific niche consumers. In this case we propose to create a demand on new specific features of traditional products or make a mainstream on new product in order to create a niche inside the big market segment. The main scientific value of article consists of original methodic of defining niche market which include seven stages. Also, example of successful creation of niche for lavender products on USA market was describing. Findings. Niche market orientation becomes important tool for creating a comparative advantages for Ukrainian enterprises. Personalization of the proposal, the development of content marketing, SMM marketing, the rapid growth of the volume of Internet commerce through mobile personalized applications shows the leads to personification of the consumer, the possibility of allocating his special tastes and preferences and adaptation of certain product groups for the needs of the most advanced niche market. The article outlines the methodology for allocating market niches and activity strategies within their boundaries, which is applicable in nature and can be used as a tool for strategic planning of enterprises.
Methodical ways to defining niche market
Keywords: ринок; ринкова ніша; маркетинг; методичний підхід; конкурентоспроможність; конкурентна перевага; market; niche market; marketing; methodical way; competitiveness; competitive advantage